Kemampuan Pemecahan Masalah Mahasiswa pada Kalkulus Integral Dilihat dari Keyakinan dan Pengetahuan Awal Matematis - Robert Harry Soesanto; Kurnia Putri Sepdikasari Dirgantoro (Jurnal Elemen, 2021)
Integral calculus is a course where students tend to have difficulties in problem-solving. This study examines differences in mathematical beliefs in students' problem-solving skills based on mathematics prior knowledge. This study's subjects were 120 students of the Mathematics Education study program from UPH Faculty of Education. The independent variable is mathematical beliefs, the moderator variable is prior mathematics knowledge, and the dependent variable is students' problem-solving skills. This study is an ex post facto quantitative research with instruments in a Likert scale questionnaire for mathematical beliefs, problem-solving, and mathematics prior knowledge test scores. Hypotheses were tested statistically with a two-way Anova test using SPSS 16.0. The results of the study were: (1) students' problem-solving of logical consistency beliefs is higher than memorized and procedural beliefs, (2) there is an interaction between mathematical beliefs and mathematics prior knowledge on problem-solving, (3) students' problem-solving in high mathematics prior knowledge group of logical consistency beliefs is higher than memorized, and procedural beliefs, and (4) students' problem-solving in low mathematics prior knowledge group of logical consistency beliefs is lower than memorized and procedural beliefs.